Reading the New Testament in the Manifold Contexts of a Globalized World Exegetical Perspectives - Becker, Eve-Marie; Herzer, Jens (A. Francke Verlag, 2022)
"This volume gathers the perspectives of teachers in higher education from all over the world on the topic of New Testament scholarship. The goal is to understand and describe the contexts and conditions under which New Testament research is carried out throughout the world. This endeavor should serve as a catalyst for new initiatives and the development of questions that determine the future directions of New Testament scholarship. At the same time, it is intended to raise awareness of the global dimensions of New Testament scholarship, especially in relation to its impact on socio-political debates. The occasion for these reflections are not least the present questions that have been posed with the corona pandemic and have received a focus on the ""system relevance"" of churches, which is openly questioned by the media. The church and theology must face this challenge. Towards that end, it is important to gather impulses and suggestions for the discipline from a variety of contexts in which different dimensions of context-related New Testament research come to the fore."